Estrategias de marketing y su impacto en la competitividad del centro de salud tipo c en el cantón la maná - García Rivera, Anais Felicita (2025)
The objective of this research project was to analyze how marketing strategies impact the competitiveness of the Type C Health Center in the La Maná canton. To this end, a mixed-method approach was applied that integrated qualitative and quantitative tools, including user surveys and an interview with the institution's director. The study allowed for an assessment of public perceptions of service quality, as well as the effectiveness of the center's promotional activities. The results showed that, currently, the Type C Health Center in La Maná faces limitations in its institutional communication capacity due to the exclusive use of traditional media and the absence of a structured marketing strategy. This situation has created a disconnect between service promotion and actual user experience, affecting perceptions of quality, community trust, and competitiveness compared to other providers. Despite having staff valued for their warmth and a wide range of services, inconsistencies in care delivery and weak institutional visibility persist, highlighting the need for strategic actions adapted to the rural context. It is concluded that the perception of quality at the Health Center is influenced by service promotion, although gaps persist between the institutional message and actual care. Competitiveness depends on operational and relational factors and can be strengthened through digital marketing and participatory communication strategies. It is recommended that institutional communication be improved through clear messages and accessible media, that a simple quality monitoring system be implemented, and that a marketing plan focused on community promotion and loyalty be developed, tailored to available resources.